Contribution on spider families Nesticidae and Pholcidae (Araneae) from Argentina - Torres, Victor (2015)
A new species of Nesticus Thorell, 1869, N. salta sp. nov.; and a new species of Guaranita Huber, 2000, G. dobby sp. nov., are described for the Chaco Serrano ecoregion of the Salta province (Argentina). The female of G. yaculica Huber, 2000 is described for the first time, and the known distribution of G. munda (Gertsch, 1982) is enlarged to Jujuy province, northern Argentina